Genuinely New: The Strategy of Remix in Live Blogs - Jasper Schelstraete (Authorship, 2013)
This article examines the strategies of remix as used to author live blogs in mainstream news media. The importance of this lies in how authorship shapes not only the form of the text but also its critical content and reading experience. Studying a variety of live blogs as used on The Guardian website, the author observes and classifies three such strategies: remix for continuity and diversity of content; for connecting digital and physical time-spaces; and for sociability on both the worldwide and mobile web. In light of the reproducibility of content in digital media, the article also re-considers the nature of digital authorship in terms of how such authorship engages in a more extensive global dialogue, adding to a glue of social media that holds together different voices across spaces.